Our Images. - Flusser, Vilém (Flusser Studies, 2013)
The article offers the author's view on technical images. The author states that technical images are instruments for creating the message of texts imaginable and aims to turn text into transparent for the concrete live experience. The author cites that technical images which are produced by men are different from the traditional images which are produced by apparatus. The author also mentions that technical images pretend to be symbolic like the traditional image.